STATUS HUBUNGAN MAHRAM PRAKTIK JUAL BELI ASI PERSPEKTIF MAZHAB HANAFI DAN MAZHAB SYAFI’I SERTA RELEVANSINYA DENGAN FATWA MUI NOMER 28 TAHUN 2013 - Prima Adhyaksa Putra; Muhammad Muhammad (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Indonesian law is still unclear about the law of buying and selling breast milk whether it has an impact on mahram relationships or not, Imam Hanafi and Imam Syafi'i have different opinions on this issue. MUI Fatwa No. 28 of 2013 and government regulation No. 33 of 2012 do not explain in detail the issue of buying and selling breast milk and its legal provisions. The purpose of this study is to find out the opinions of the Hanafi and Syafi'i madhabs regarding the law of mahram relationship status of breast milk sale and purchase practices and whose opinion is more relevant to MUI Fatwa No. 28 of 2013. This type of research is library research, and the nature of this research is included in analytic descriptive research. The sources in this study are secondary data consisting of primary legal materials and secondary legal materials. The primary legal material is the Koran, hadith, scriptures and other books. Meanwhile, secondary legal material is data that supports official document data sources. According to Imam Abu Hanifah, breast milk that has separated from the woman's breast, has changed its status to carrion, is not included in the category of property and is an honorable part of the human body that cannot be traded. Meanwhile, according to Imam Syafi'i, breast milk is not forbidden to consume and is a sacred object and can be taken advantage of, so the law resembles animal milk and is allowed to be traded. In addition, there are also differences regarding the number or form of breastfeeding that can make it forbidden. Imam Syafi'i is of the opinion that five separate breastfeedings are permissible, and they derive their ruling from the hadiths narrated by 'Aa'ishah, because they consider 'Aa'ishah to be the most knowledgeable of the ruling on this issue among the Muhammadans. The Hanafis, on the other hand, were of the view that even one breastfeeding can lead to prohibition by taking the muthlaq of the Qur'an, because what is forbidden according to the text of the Qur'an is breastfeeding, and breastfeeding is only one breastfeeding. While breastfeeding is an act that can forbid marriage. Then the relationship with MUI Fatwa No. 28 of 2013 leads to the opinion of the Hanafi school of thought because breast milk is part of the human body that cannot be traded.